Learning Strategy of Successful Students in An Online Intermediate Grammar Class - Katarina Ramita Tania (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
This study aims to investigate the learning strategies of successful students in an online intermediate grammar class. The research participants were all English as Foreign Language (EFL) students, batches 2019 and 2020, 2021, who got an A or AB in intermediate grammar class at the English Language Education Program (ELEP), Universitas Kristen Satya Wacana (UKSW). Open-ended questionnaires and interviews were used as the instruments to collect the data. In the questionnaire, 49 participants were asked to respond to several statements. At the same time, in the interview process,  the researcher involved 6 participants to clarify their responses to the questionnaire. The data analysis revealed three grammar learning strategies that could make students successful in their grammar class: (1) determining difficult grammatical structures and trying to learn the difficulty; (2) paying attention to grammatical structures when translating sentences; and (3) taking notes when the teacher explains a new grammatical structure.